Impact of Environmental, Social, and Governance (ESG), Profitability and Macroeconomics Indicators on Firm Performance - Ma’in, Masturah; Asmuni, Shahariah; Junos, Sutina; Rostam, Siti Nurhafiza; Azmi, Noor Hidayatul Aqmar; Sahidza, Khairunnisa Rabiah (Journal of Entrepreneurship, Business and Economics; Vol 10 No 2 (2022): Theme: Contemporary Issues in Business and Management, 2022)
Firms that are ESG compliant have better governance, care more about the environment and sustainable development, have lower profits volatility and access to lower-cost funding.  Many investors can easily make judgment based on firm performance rather than financial success if ESG is incorporated into a firm's investment decision. The purpose of this study is to examine the relationship between ESG score, profitability, growth domestic product (GDP) growth, labor force, and population with Malaysian firms’ performance. A multiple regression technique is used to estimate the ordinary least square (OLS) method from year 2010 to 2020. The result identifies that ESG score, GDP growth, and population has significant relationship with firm performance. Research paper Keywords: Firm Performance; ESG; Profitability; Macroeconomic Indicators; Malaysia Reference to this paper should be made as follows: Ma’in, M., Asmuni, S., Junos, S., Rostam, S. N., Azmi, N. H. A., & Sahidza, K. R. (2022). Impact of Environmental, Social, and Governance (ESG), Profitability and Macroeconomics Indicators on Firm Performance. Journal of Entrepreneurship, Business and Economics , 10 (2), 1–17.